Optimization of the process extraction and drug release of fish gelatin nanoparticles derived from tilapia (oreochromis spp) - Subara, Deni (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
Gelatin is one of the popular biopolymers used for food and pharmaceutical applications, given its capability to dissolve in aqueous environments and to form nanoparticles that enable the encapsulation of various active agents into stable products. On the other hand, coupled with these capabilities and recognition by the US Food and Drug Administration (FDA) authority, as Generally Recognized as Safe (GRAS) material, it has attracted growing interest and attention from researchers to produce gelatin nanoparticles toward encapsulating various food and pharmaceutical molecules. However, even though gelatin can be produced from mammalian and fish, it is quite challenging since all sources of gelatin nanoparticles in the market originate from mammalian gelatin, which is either bovine or porcine. Although the use of such gelatin as highlighted by Muslims, Jews, and other religious backgrounds is an issue. Furthermore, there are no publications regarding gelatin nanoparticles from fish gelatin published at this stage, which further adds to this problem. Therefore, this study aims to prepare and characterize fish gelatin nanoparticles (FGNPs) and FGNPs encapsulated with an active agent. Fish gelatin was first extracted from Tilapia fish skin employing a two-step desolvation method in producing FGNPs. The initial first desolvation step was optimized to obtain consistent high molecular weight at the gelatin concentration, temperature, centrifugation speed, and centrifugation time of 9%, 45 °C, 12000 xg, and 5 min, respectively. As an outcome from this work, a new method to produce significant FGNP properties consistently was created based on this step. A second desolvation step adopting the two-step desolvation method was also optimized in which significant factors were screened using Plackett-Burman experimental design, determining that the pH, acetone percentage, and glutaraldehyde volume were the significant factors. These factors were then optimized using factorial design, indicating that FGNPs with a size of 198.46 ± 6.1 nm were produced using pH, acetone concentration, and a glutaraldehyde volume of 2.45, 16%, and 400 µl, respectively. Indeed, increasing pH and acetone concentration led to an increase in the size of particles, whereas increasing the volume of glutaraldehyde decreased the size of FGNPs. Accordingly, this work makes a valuable contribution by developing an optimized production process, thereby demonstrating the potential for the future application of FGNPs. This study has also shown that fish gelatin could be used as an alternative for mammalian gelatin for producing nanoparticles. Here, the production process of drug-loaded FGNPs was optimized in which the significant factors were screened using factorial design for encapsulation efficiency. The drug amount was also found to have a significant effect, whereas pH, acetone percentage, and the glutaraldehyde amount with stirring time was not significant concerning the encapsulation efficiency of drug-loaded FGNPs. Notably, increasing the drug amount increased encapsulation of drug-loaded FGNPs in which an encapsulation efficiency of 39%, was observed. The physicochemical characterization of the optimum formulation, as suggested, was also examined using a Scanning electron microscope (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM) showing FGNPs having a smooth surface. Fourier-transform infrared diffraction (FTIR) revealed the presence of the drug in tailored FGNPs, and Powder X-ray diffraction (XRD) analysis highlighted the formation of amorphously dispersed systems having a slightly faster release profile of drug-loaded FGNPs with a biphasic release profile. The release mechanism followed non-fickian diffusion, meaning that the release of the drug from FGNPs was governed by diffusion and erosion of the matrix.